Effectiveness of clinician client-centered counseling on knowledge, attitudes and sexual bahaviors of antiretroviral therapy patients in Yola, Nigeria - Martins, Olutayo Folashade (2015)
Background: HIV/AIDS is a major challenge to public health in recent times. An estimated 34.0 million people are living with HIV/AIDS globally. Nearly one in twenty adults (4.9%) are living with HIV in Sub- Saharan Africa accounting for about 69% of the global burden. Prevalence in Nigeria is 4.1%. Adamawa state with Yola as capital has a prevalence of 3.8%.Despite better awareness and understanding of HIV in Nigeria, unhealthy sexual behaviors such as;continued unprotected sexual intercourse among HIV positive individuals with partners who are HIV negative or of unknown status, none or inconsistent condom use, multiple sexual partners and non-disclosure of status to spouses and/or sexual partners are noted. Thus behavioral change preventive interventions are still a driving force against HIV. Objective: To develop, implement and evaluate the effectiveness of a clinician client centered counseling module on improving knowledge on HIV transmission and prevention, attitudes towards HIV/AIDS, reducing multiple sexual partners, improving condom use and increasing HIV status disclosure to spouse/sex partners of ART patients in Yola, Nigeria. Methodology: This study was a three arm randomized single blind clinical trial involving 386 randomly selected and allocated adult HIV patients who were enrolled into Antiretroviral Therapy (ART) at all four comprehensive ART sites in Yola. A clinician client centered training module was developed based on the Information Behavior and Motivation (IBM) Model. Nine Clinicians were trained with this module to deliver a 10 to 15 minutes clinic based intervention (Clinician client centered counseling). The three groups were; intervention group one, intervention group two and the control group. Intervention group one received two counseling sessions; at baseline then at two months. Intervention group two received one counseling session at baseline only and the control group received routine care. An interviewer administered validated and reliable structured questionnaire was used for data collection. Data was collected at baseline, two months and six months. Outcome measures included;knowledge on HIV transmission and prevention, attitudes towards HIV/AIDS,number of sexual partners, frequency of condom use and status disclosure rates. Data was analyzed using SPSS version 22. Test of significance was at α level 0.05. Results: A significant statistical effect was seen for group (F (2, 331) = 17.410,p = 0.0001), time (F (2) = 49.826, p = 0.0001) and group and time interaction (F (2, 331) = 4.239, p = 0.002) for HIV knowledge. There was a significant main effect for groups (F (2) =11.107, p = 0.0001) and time (F (2) = 34.088, p = 0.0001) for attitudes towards HIV/AIDS. A significant change in median condom use scores from baseline to six months was seen for intervention group one;Friedman’s ANOVA ( ) = 12.410, p = 0.002. There was a significant main effect for time (F (2, 219) = 4.093, p = 0.020) for HIV status disclosure to spouse and/or sexual partners. Reductions were seen in numbers of respondents who had sex with unsteady partners in all study groups. Conclusion: Clinician client centered counseling is an effective behavioral intervention in improving knowledge, attitudes and sexual behaviors of ART patients.